ANALISIS YURIDIS PENEMBAKAN OLEH POLISI TERHADAP PELAKU YANG DIDUGA MELAKUKAN TINDAK PIDANA DIKAITKAN DENGAN ASAS PRADUGA TIDAK BERSALAH - Tabah Santoso; Erdianto Effendi; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesian National Police (INP) is in the Indonesian National Police, which is responsible directly under the President. The Police carry out policing duties throughout Indonesia. Article 18 paragraph (1) of Law No. 2 of 2002 on the Indonesian National Police provides: